Pneumococcal Polysaccharide Vaccination Elicits IgG Anti-A/B Blood Group Antibodies in Healthy Individuals and Patients with Type I Diabetes Mellitus - Wolfram, Wendelin; Sauerwein, Kai M. T.; Binder, Christoph J.; Eibl-Musil, Nicole; Wolf, Hermann M.; Fischer, Michael B. (Frontiers in Immunology, 2016)
Hypothesis: Blood group antibodies are natural antibodies that develop early in life in response to cross-reactive environmental antigens in the absence of antigen encounter. Even later in life structural similarities in saccharide composition between environmental antigens such as bacterial polysaccharides and blood group A/B antigens could lead to changes in serum levels, IgM/IgG isotype and affinity maturation of blood group anti-A/B antibodies. We adressed the question whether immunization with pneumococcal polysaccharide (PnP) vaccine (PPV) Pneumovax®23 could have such an effect in patients with with type I diabetes mellitus (DM I), an autoimmune disease where an aberrant immune response to microbial antigens likely plays a role. Methods: Anti-PnP IgM and IgG responses were determined by ELISA and the Diamed-ID Micro Typing System was used to screen anti-A/B antibody titer before and after Pneumovax®23 immunization in 28 healthy individuals and 16 patients with DM I. In addition, surface plasmon resonance (SPR) technology using the Biacore® device and a synthetic blood group A/B trisaccharide as the antigen was applied to investigate IgM and IgG anti-A/B antibodies and to measure antibody binding dynamics. Results: All healthy individuals and DM I patients responded with anti-PnP IgM and IgG antibody production four to six weeks after Pneumovax®23 (Pn23) immunization, while no increase in blood group anti-A/B antibody titer was observed when measured by the Diamed-ID Micro Typing System. Interestingly, isotype-specific testing by SPR-technology revealed an increase in blood group anti-A/B IgG, but not IgM, following Pn23 immunization in both patients and controls. No change in binding characteristics of blood group anti-A/B antibodies could be detected following Pn23 vaccination, supporting the assumption of an increase in IgG antibody titer with no or very little affinity maturation. Conclusion: The study provides evidence for epitope sharing between pneumococcal polysaccharides and blood-group ABO antigens which leads to a booster of blood group anti-A/B antibodies of the IgG isotype after Pneumovax®23 immunization in healthy individuals. Manifest autoimmunity such as present in DMI patients has no additional effect on the cross-reactive antibody response against pneumococcal polysaccharides and blood group antigens.